2019
DOI: 10.1002/art.41063
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Conventional Uric Acid–Lowering Therapy on Monosodium Urate Crystal Deposits

Abstract: Objective Few studies have systematically and quantitatively addressed the impact of urate‐lowering therapy on monosodium urate (MSU) deposits. This study was undertaken to analyze the effect of lifestyle measures and conventional urate‐lowering therapy on MSU deposits in patients with gout. Methods In this prospective study, subjects with gout according to the American College of Rheumatology/European League Against Rheumatism classification criteria and presence of MSU deposits seen on dual‐energy computed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 29 publications
1
13
0
6
Order By: Relevance
“…At the upper therapeutic range of SU up to 0.43 mmol/l (7.2 mg/dl), some degree of dissolution is still possible within a reasonable time frame. This is consistent with the finding that tophi could be partly resolved on DECT over 22 ± 11 months through lifestyle change alone when SU was brought down to an average of 6.7 ± 1.7 mg/dl [30]. However, complete dissolution is impractical if SU > 0.36 mmol (6 mg/dl).…”
Section: Discussionsupporting
confidence: 88%
“…At the upper therapeutic range of SU up to 0.43 mmol/l (7.2 mg/dl), some degree of dissolution is still possible within a reasonable time frame. This is consistent with the finding that tophi could be partly resolved on DECT over 22 ± 11 months through lifestyle change alone when SU was brought down to an average of 6.7 ± 1.7 mg/dl [30]. However, complete dissolution is impractical if SU > 0.36 mmol (6 mg/dl).…”
Section: Discussionsupporting
confidence: 88%
“…The traditional treatment for gout attack has been well established for improvement of quality of life, although treatment with ULT alone may not be optimal for patients [90]. The current recommendation is additionally to employ anti-inflammatory therapy [91] and to reduce pathologic MSU deposition [92]. Commencing ULT alone during an acute gout attack could have neither significant efficacy on localized pain, recurrent flares, or adverse effects [48] nor been associated with the risk of gout flare [93], or able to ameliorate gout associated diabetes incidence or reverse beta-cell apoptosis with significance [94] or improvement of kidney function [95].…”
Section: Therapeutic Regimes For Treatments Of Hyperuricemia and Goutmentioning
confidence: 99%
“…In the past, reports already con rmed that high serum uric acid increased the burden of monosodium urate (MSU) deposits. [20,21] Previous studies reported that MSU deposits would lead to structural damage in corresponding organs where the MSU deposits were found. A nephrological research found that high SUA led to uric acid super saturated in the urine, and supersaturation in the urine increased monosodium urate (MSU) deposits in the kidney formed uric acid stones.…”
Section: Smooth Curve Ttingmentioning
confidence: 99%